WORKSHOP PROJECT BASED LEARNING DAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) BAGI GURU-GURU MATA PELAJARAN GEOGRAFI SMA SE-KABUPATEN TASIKMALAYA - Novianty, Ane; Rohayati, Dedeh (Universitas Mataram, 2024)
The implementation of a merdeka’s curriculum remains a complex issue, both in the development of educational modules and P5. Similar to the MGMP of Geography in Tasikmalaya District, since the introduction of the independent curriculum, none of the MGMP councils has made a substantial contribution to its preparation and implementation, especially in the educational modules. In fact, 5 secondary schools have now implemented the Merdeka’s Curriculum (preparatory stage) and 64 other schools are still using the 2013 curriculum. Community services are bundled with geography subject teaching and P5 module development workshops. Expected outcome goals include: 1) Increase knowledge about preparing frrameworks for project-based learning models for geography subjects; 2) Increase a knowledge to create a design framework for a geography subject project to link with other subjects in the P5. All participats in the four groups experienced an increase in knowledge (100%). However, from a project-based learning perspective, each group can be considered highly interactive. The FGD results concluded that the following was taken into account when preparing the P5 teaching module: 1) Possibilities in the school environment; 2) Adapt to the values of local wisdom that exist in each region; 3) Sustainable time management; and 4) In P5, the contribution of geography subjects is high.